PROSPECTS OF USING LOCAL PLANT RAW MATERIALS IN LACTOSE-FREE DRINK LASSI - Силка, Ірина; Петров, Євген (SWorldJournal, 2024)
The article considers the prospect of adapting an Indian drink for a wider range of consumers with the possibility of using local raw materials, namely pureed sea buckthorn berries and blueberries. Lactose-free yogurt based on Lactobacillus rhamnosus stra